La violenza narrata. Storie di abusi e maltrattamenti maschili sulle donne (Società e diritti, 2025)
In this contribution she analyzes male violence against women, from an innovative analytical perspective, we try to understand gender abuse through the narratives of some social workers, who every day look for models of contrast and help towards abused women, but also some stories of violent men, definitively convicted of crimes such as femicides or sexual violence. A qualitative approach will be used, with semi-structured interviews, a great work by social workers emerges in the research, while in the stories of violent men all the cultural negativity against the female gender emerges, moreover an important result is the neutralizations that these men put in place to justify the guilt and often the responsibility of violent events, it is projected towards the victim, the real responsible for the violence.